Kontaminasi pestisida organofosfat dan logam berat pada airtanah di Wilayah Pantai Utara Jawa Tengah dan Jawa Timur - B Tyas Susanti; Baskoro Rochaddi; Chrisna Adhi Suryono; Irwani Irwani (Jurnal Kelautan Tropis, 2020)
Groundwater is the main source of clean fresh water in coastal areas. Coastal cities development in many sectors often produces waste that pollutes groundwater, among others, in the form of pesticides and heavy metals. Chlorpyrifos, mercury and arsenic are contaminants that are toxic and endanger human health or the environment. The purpose of this study was to examine groundwater conditions against contamination of organophosphate pesticides, heavy metals Hg and As in the northern coastal areas of Central Java and East Java. Chlorpyrifos content was found in 4 sample locations with a concentration of 0.0004 - 0.0021 ppm. Hg content was found at 8 sample locations with a concentration of 0.004 - 0.321 ppm and As was found at all locations (26) samples with a concentration of 0.102 - 0.505 ppm. The results of the analysis show that the incidence of pesticides and heavy metals in groundwater has anthropogenic sources due to agricultural, industrial or residential waste activities.  Airtanah merupakan sumber daya air tawar bersih yang utama di wilayah pesisir. Perkembangan kota-kota pesisir di banyak sektor seringkali menghasilkan limbah yang mencemari airtanah antara lain berupa pestisida dan logam berat. Khlorpirifos, merkuri dan arsen merupakan kontaminan yang bersifat toksik dan membahayakan kesehatan manusia ataupun lingkungan. Tujuan penelitian ini mengkaji kondisi airtanah terhadap kontaminasi pestisida organofosfat, logam berat Hg dan As di daerah pantai utara Jawa Tengah dan Jawa Timur. Kandungan khlorpirifos ditemukan di 4 lokasi sampel dengan konsentrasi 0,0004 – 0,0021 ppm. Kandungan Hg ditemukan pada 8 lokasi sampel dengan konsentrasi 0,004 – 0,321 ppm dan As ditemukan pada semua lokasi (26) sampel dengan konsentrasi 0,102 – 0,505 ppm. Hasil analisis menunjukkan kejadian pestisida dan logam berat pada airtanah bersumber antropogenik akibat kegiatan pertanian,  industri atau limbah pemukiman.